Optimal Risk-Return Trade-Offs of Commercial Banks and the Suitability of Profitability Measures for Loan Portfolios - Kühn, Jochen (Lecture Notes in Economics and Mathematical Systems, 2006)
The present book criticizes the fact that profitability measures derived from capital market models such as the Sharpe ratio and the reward-to-VaR ratio are proposed for loan portfolios although it is not assessed whether their risk-return trade-offs are optimal for banks. This volume intends to fill this gap. The approach of this work is to endogenously derive optimal risk-return trade-offs of commercial banks and to compare them with those of reward-to-risk ratios. The risk-return trade-offs for banks are derived taking into account market discipline, Basel I and Basel II regulatory capital requirements, and insured deposits. It is found that even the reward-to-VaR ratio, which is explicitly developed for the purpose of valuating loan portfolios, can be highly misleading. The volume also helps in understanding risk management motives of banks, in particular, how market discipline, capital requirements, and insured deposits affect the decision-making of banks.